Autophagy is required for human umbilical cord mesenchymal stem cells to improve spatial working memory in APP/PS1 transgenic mouse model - Wen Li; Kai Li; Jing Gao; Zhuo Yang (Stem Cell Research & Therapy, 2018)
Abstract Background Recent studies have shown that autophagy plays a central role in mesenchymal stem cells (MSCs), and many studies have shown that human umbilical cord MSCs (huMSCs) can treat Alzheimer’s disease (AD) through a variety of mechanisms. However, no studies have looked at the effects of autophagy on neuroprotective function of huMSCs in the AD mouse model. Thus, in this study we investigated whether inhibition of autophagy could weaken or block the function of huMSCs through in vitro and in vivo experiments. Methods In vitro we examined huMSC migration and neuronal differentiation by inhibiting or activating autophagy; in vivo autophagy of huMSCs was inhibited by knocking down Beclin 1, and these huMSCs were transplanted into the APP/PS1 transgenic mouse. A series of related indicators were detected by T-maze task, electrophysiological experiments, immunofluorescence staining, enzyme-linked immunosorbent assay (ELISA), and Western blotting. Results We demonstrated that regulation of autophagy can affect huMSC migration and their neuronal differentiation. Moreover, inhibition of autophagy in huMSCs could not realize neuroprotective effects via anti-apoptosis or promoting neurogenesis and synapse formation compared with those of control huMSCs. Conclusions These findings indicate that autophagy is required for huMSCs to maintain their function and improve cognition impairment in APP/PS1 transgenic mice.